2013
DOI: 10.1177/0022034513505620
|View full text |Cite
|
Sign up to set email alerts
|

Pain Fiber Anesthetic Reduces Brainstem Fos after Tooth Extraction

Abstract: We recently demonstrated that pain-sensing neurons in the trigeminal system can be selectively anesthetized by co-application of QX-314 with the TRPV1 receptor agonist, capsaicin (QX cocktail). Here we examined whether this new anesthetic strategy can block the neuronal changes in the brainstem following molar tooth extraction in the rat. Adult male Sprague-Dawley rats received infiltration injection of anesthetic 10 min prior to lower molar tooth extraction. Neuronal activation was determined by immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…TRP channels in the sensory neurons have been targeted to develop pain-specific local anesthesia in an animal study [270]. Capsaicin (a TRPV1 activator) has been combined with a permanently charged derivative of lidocaine, QX-314, and this combination appears to be effective as a local anesthetic [271,272,273]. An animal study demonstrated that local application of this drug combination in the gingiva near a tooth before extraction reduced extraction-induced neuronal activation, indicated by reduced expression of c-Fos in the brainstem trigeminal subnucleus caudalis [273].…”
Section: Clinical Significancementioning
confidence: 99%
See 1 more Smart Citation
“…TRP channels in the sensory neurons have been targeted to develop pain-specific local anesthesia in an animal study [270]. Capsaicin (a TRPV1 activator) has been combined with a permanently charged derivative of lidocaine, QX-314, and this combination appears to be effective as a local anesthetic [271,272,273]. An animal study demonstrated that local application of this drug combination in the gingiva near a tooth before extraction reduced extraction-induced neuronal activation, indicated by reduced expression of c-Fos in the brainstem trigeminal subnucleus caudalis [273].…”
Section: Clinical Significancementioning
confidence: 99%
“…Capsaicin (a TRPV1 activator) has been combined with a permanently charged derivative of lidocaine, QX-314, and this combination appears to be effective as a local anesthetic [271,272,273]. An animal study demonstrated that local application of this drug combination in the gingiva near a tooth before extraction reduced extraction-induced neuronal activation, indicated by reduced expression of c-Fos in the brainstem trigeminal subnucleus caudalis [273]. Eugenol was reported to sensitize and then desensitize TRPV1 channels, which may explain the pain suppressing action of zinc oxide eugenol cements used in temporary restorations of carious teeth [274].…”
Section: Clinical Significancementioning
confidence: 99%
“…and were transcardially perfused sequentially with PBS (0.01 M) followed by paraformaldehyde (4% in PBS). c-fos immuno-labelling was performed according to previously published methods [8]. The lumbar spinal cord was removed for post-fixation overnight and cryopreserved in 30% sucrose for 3-4 weeks at 4°C.…”
Section: Spinal C-fos Assessmentmentioning
confidence: 99%